Maxwell's equations and Lorentz transformations. (1st May 2022) - Aguirregabiria, J M; Hernández, A; Rivas, M
Abstract: We explore the possibility of introducing the special relativity to undergraduate students by restricting the relativity principle to Maxwell's equations in vacuum. By making some hypothesis of simplicity, we obtain the transformation equations for the electric and magnetic fields among equivalent observers. Later, the transformation equations for the charge and current density are found and, finally, the Lorentz transformations. What is left is to extend the relativity principle to all physical phenomena.